2023
DOI: 10.3390/vaccines11020456
|View full text |Cite|
|
Sign up to set email alerts
|

Platelet Activation and Cytokine Release of Interleukin-8 and Interferon-Gamma-Induced Protein 10 after ChAdOx1 nCoV-19 Coronavirus Vaccine Injection

Abstract: Coronavirus disease 2019 (COVID-19) vaccines are associated with serious thromboembolic or thrombocytopenic events including vaccine-induced immune thrombocytopenia and thrombosis and immune thrombocytopenia, particularly AZD1222/ChAdOx1. According to the proposed mechanism, COVID-19 vaccines stimulate inflammation and platelet activation. In this study, we analyzed the role of AZD1222/ChAdOx1 vaccines in the activation of platelets and the release of anti-PF4 antibodies and inflammatory cytokines in a cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…It was suggested that this side effect is a result of the immune response to the vaccine, activation of endometrial immune cells that regulate the generation of the endometrium, or immunological influence on the secretion of follicular stimulating hormone (FSH) and luteinizing hormone (LH) 4 , 9 , 15 . Examination of the COVID-19 vaccine pointed to an immunologic response, manifested by cytokine release (as Interleukin-8; IL-8) 16 . However, a direct effect of the vaccine on the ovary should be examined, as recent papers showed that ovarian cells could be directly infected by the SARS-CoV-2 virus 17 , and that the vaccine caused a biological response similar to that of prolactin signaling, which may lead to short-term menstrual irregularities 18 .…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that this side effect is a result of the immune response to the vaccine, activation of endometrial immune cells that regulate the generation of the endometrium, or immunological influence on the secretion of follicular stimulating hormone (FSH) and luteinizing hormone (LH) 4 , 9 , 15 . Examination of the COVID-19 vaccine pointed to an immunologic response, manifested by cytokine release (as Interleukin-8; IL-8) 16 . However, a direct effect of the vaccine on the ovary should be examined, as recent papers showed that ovarian cells could be directly infected by the SARS-CoV-2 virus 17 , and that the vaccine caused a biological response similar to that of prolactin signaling, which may lead to short-term menstrual irregularities 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors wish to make the following corrections to this published paper [1]. Due to the authors' oversight, Figures 3 and 4 In addition, the authors would also like to correct the typing errors.…”
mentioning
confidence: 99%